Epigenetic screen of human DNA repair genes identifies aberrant promoter methylation of NEIL1 in head and neck squamous cell carcinoma - Chaisaingmongkol, Jittiporn; Warta, Rolf; Dyckhoff, Gerhard; Herpel, Esther; Campos, Benito; Lorenzo Bermejo, Justo; Herold-Mende, Christel (Oncogene, 2012)
Aberrant promoter methylation of different DNA repair genes has a critical role in the development and progression of various cancer types, including head and neck squamous cell carcinomas (HNSCCs). A systematic analysis of known human repair genes for promoter methylation is however missing. We generated quantitative promoter methylation profiles in single CpG units of 160 human DNA repair genes in a set of DNAs isolated from fresh frozen HNSCC and normal tissues using MassARRAY technology. Ninety-eight percent of these genes contained CpG islands (CGIs) in their promoter region; thus, DNA methylation is a potential regulatory mechanism. Methylation data were obtained for 145 genes, from which 15 genes exhibited more than a 20% difference in methylation levels between tumor and normal tissues, manifested either as hypermethylation or as hypomethylation. Analyses of promoter methylation with mRNA expression identified the DNA glycosylase NEIL1 (nei endonuclease VIII-like 1) as the most prominent candidate gene. NEIL1 promoter hypermethylation was confirmed in additional fresh frozen HNSCC samples, normal mucosa, HNSCC cell lines and primary human skin keratinocytes. The investigation of laser-microdissected tissues further substantiated increased methylation levels in tumor versus matched non-tumor cells. Immunohistological analysis revealed significantly less NEIL1 protein expression in tumor tissues. 5-Aza-2′-deoxycytidine treatment and DNMT1 knockdown resulted in the re-expression of NEIL1 in HNSCC cell lines, which initially carried hypermethylated promoter regions. In conclusion, our results suggest that DNA methylation contributes to the downregulation of NEIL1 expression and might thus have a role in modulating the response to therapies of HNSCC.